2014
DOI: 10.5367/te.2013.0343
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price Dispersion on hOtel Performance

Abstract: Previous studies have concentrated on comparing price dispersion and price level between offline and online channels. The primary objectives of this study are to (a) investigate the relationships between offline price dispersion and a company's performance, (b) examine the relationships between online price dispersion and a company's performance and (c) investigate the effect of price dispersion between offline and online channels on a company's performance. The findings show that a decrease in online price di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 104 publications
(133 reference statements)
0
18
0
1
Order By: Relevance
“…In addition, new information guests obtain on room pricing after booking may influence their decisions to cancel (Chen et al, 2011). It is well known that price transparency is higher in the online booking environment (Kim, Cho, Kim, and Shin, 2014), which is another factor that suggests OTA bookings are more likely to be cancelled than offline reservations. Empirical evidence also bears out the importance of the distribution channel at hand in predicting cancellations (Morales and Wang, 2010;Antonio et al, 2017).…”
Section: Theoretical Background and Formulation Of Hypothesesmentioning
confidence: 99%
“…In addition, new information guests obtain on room pricing after booking may influence their decisions to cancel (Chen et al, 2011). It is well known that price transparency is higher in the online booking environment (Kim, Cho, Kim, and Shin, 2014), which is another factor that suggests OTA bookings are more likely to be cancelled than offline reservations. Empirical evidence also bears out the importance of the distribution channel at hand in predicting cancellations (Morales and Wang, 2010;Antonio et al, 2017).…”
Section: Theoretical Background and Formulation Of Hypothesesmentioning
confidence: 99%
“…The proliferation of Internet commerce has changed the way firms consider and develop their pricing strategies. Traditional offline channels often employed price discrimination (i.e., offering different prices to different segments of consumers) as a key pricing strategy (e.g., Brynjolfsson and Smith 2000; Gerardi and Shapiro 2009), often resulting in price dispersion between these segments both online and offline (W. G. Kim et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…G. Kim et al 2014). Price dispersion refers to the variation of price between the highest and lowest prices across different sellers for the same goods and services (Clemons, Hann, and Hitt 2002; W. G. Kim et al 2014; Pan, Ratchford, and Shankar 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dynamic pricing models and dynamic pricing structures have shown to be very prevalent and central in the success of online distribution channels (Guo,et al, 2013). Kim, Cho, Kim, and Shin (2014) found that the proliferation of channels led to matching pricing and dates of when the sale occurs with customer expectations. Maier (2012) argued that hotels need to be more focused on consistent pricing across all channels.…”
Section: Pricementioning
confidence: 99%
“…Hung, Shang, and Wang (2010) argued that hotels needed to take into account market supply, demand, seasonality, and revenue pricing strategies when setting rates. Kim, et al, (2014) found that the variability of pricing negatively influenced hotel performance of online channels. Zhang, et al, (2011) found that variables like the size, age, and location of the hotel significantly impacted hotel room prices.…”
Section: Top-line Revenuementioning
confidence: 99%